Improvement of Selected Soil Chemical Properties and Potassium Uptake by Mung Beans After Application of Liquid Organic Fertilizer in Ultisol - Tristantia Anggita; Zainal Muktamar; Fahrurrozi Fahrurrozi (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2018)
Recently, application of liquid organic fertilizer (LOF) in organic farming practices is of importance to prevent further soil degradation due to prolong and massive use of synthetic fertilizer. LOF provides faster plant nutrients than soil organic fertilizer. However, quality of LOF is substantially dependent on its sources. Animal wastes from rabbit, goat, and cattle are scarcely used as sources of LOF production. The study aimed to determine soil chemical improvement and potassium uptake by mung bean as affected by LOF in Ultisol. The experiment was conducted at the Greenhouse Faculty of Agriculture, employing Completely Randomized Design with two factors. The first factor was animal wastes, consisting of goat, rabbit, and cattle wastes. The second factor was LOF concentration, consisting of 0%, 25%, 50%, 75%, and 100% LOF. LOF was prepared by mixing altogether animal feces, urine, soil, green biomass, EM-4 and fresh water to total volume of 10 l in a plastic container. LOF was decanted to the polybag every week starting at one week after planting for four weeks to a total volume of 750 ml per polybag. Variables observed included soil pH, total organic-C, exchangeable K, soil nitrate-N, K concentration in plant tissue, K-uptake, and shoot dry weight of sweet corn The result showed that application of LOF from rabbit waste had the highest increment of soil pH as compared to the other treatment. However, exchangeable K was observed highest at the treatment of LOF from goat waste. Sources of LOF from animal wastes did not have an effect on K-uptake by mung bean. In addition, application of LOF up to 100% was able to improve soil chemical properties as indicated by the increase in soil pH and exchangeable K. So did the concentration and uptake of K, as well as shoot dry weight. Fertilization with LOF has benefit to the improvement of soil chemical properties leading to better K uptake.